10. SCIENTIFIC EVALUATION OF POSTOPERATIVE ANALGESIC EFFICACY OF CONTINUOUS FASCIA ILIACA COMPARTMENT BLOCK IN HIP ARTHROPLASTY AT TRANSPORT HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the postoperative analgesic efficacy of continuous fascia iliaca compartment block (FICB) using 0.1% bupivacaine after total hip arthroplasty, and to record associated adverse effects. Methods: A prospective, randomized, controlled trial was conducted on 60 patients undergoing hip arthroplasty, randomized into two groups: MC group (n=30) received continuous FICB and TKD group (n=30) received continuous femoral nerve block. Both techniques used bupivacaine and were performed under ultrasound guidance. Results: Mean VAS scores at rest and during movement in both groups were
Keywords: fascia iliaca compartment block, hip arthroplasty, bupivacaine.